Light-induced exacerbation of retinal degeneration in a rat model of Smith–Lemli–Opitz syndrome - Vaughan, Dana K. (2005)
Potentiation of retinal degeneration by intense light exposure, and its amelioration by an antioxidant, were studied in a rat model of Smith–Lemli–Opitz syndrome (SLOS), in comparison with normal (control) Sprague–Dawley rats. The SLOS model is created by treating rats with AY9944, a selective inhibitor of cholesterol synthesis at the level of 3β-hydroxysterol-Δ(7)-reductase. A subset of rats was treated with dimethylthiourea (DMTU), a synthetic antioxidant, 24 and 1 hr prior to light exposure. Half of the animals (±DMTU) were exposed to intense, constant, green light (24 hr, 1700 lx, 490–580 nm), while the others were maintained in darkness. Subsequently all animals were returned to dim cyclic light (20–40 lx, 12 hr light–12 hr dark) for 2 weeks, after which electroretinograms were recorded. One eye from each rat was taken for histological and quantitative morphometric analyses; sterol analysis was performed on retinas from contralateral eyes. HPLC analysis confirmed the accumulation of 7-dehydrocholesterol (7DHC) in retinas of AY9944-treated rats; cholesterol represented >99% of the sterol in control retinas. Histology of retinas from unexposed, AY9944-treated rats (6-week-old) was normal. In contrast, age-matched, light-exposed rats exhibited massive photoreceptor cell loss in both the superior and inferior hemispheres, and concomitant rod and cone dysfunction. The severity and geographic extent of the damage was far greater than that observed in normal albino rats exposed to the same conditions. DMTU pre-treatment largely prevented these degenerative changes. These findings indicate that the AY9944-induced rat SLOS model is hypersensitive to intense light-induced retinal damage, relative to normal rats. DMTU protection against light-induced damage implicates free radical-based oxidation in the retinal degeneration process. Furthermore, the use of green light (corresponding to the absorption maxima of rhodopsin) implicates rhodopsin in the initiation of the pathobiological mechanism. We propose that generation of cytotoxic oxysterols (by-products of 7DHC oxidation) is an integral part of retinal cell death in the SLOS rat model, which is exacerbated by intense light. Furthermore, the results predict light-dependent potentiation of retinal degeneration in SLOS patients, and the possible ameliorative effects of antioxidant therapy.